Students’ Perception on the Video Project Assignment in Practicing Speaking Skill in Senior High School - Wati, Gustina; Syafryadin, Syafryadin (LPPM Universitas Pancasakti Tegal, 2022)
This research is descriptive quantitative research that aimed to investigate the positive or negative perception of high school students toward the video project assignment in practicing their speaking skills. The population of this research was the tenth-grade of science students at SMAN 8 Kota Bengkulu in the academic year 2021/2022. The samples of the research were 65 students from two classes chosen from four science classes in the tenth grade by using random cluster sampling and the instrument was a questionnaire. The questionnaire consists of 20 items of three aspects: (1) Language English Proficiency; (2) Usage of Technological Tools in the project; and (3) Collaboration Among Peers. The result showed that video project assignments help and facilitate students in practicing English speaking skills with enhanced their English language proficiency with positive perception reaching 82.15%, it involved the use of technological tools in learning with positive perception reached 77.23% and promoted collaboration among peers also with positive perception came 87.38%. Therefore, it can be concluded that senior high school students positively perceived the video project assignment in practicing English speaking skills. Keywords: Student’s Perception, Video Project, Speaking skill